2019
DOI: 10.1002/pon.5071
|View full text |Cite
|
Sign up to set email alerts
|

Strength of belief: Religious commitment, knowledge, and HPV vaccination adherence

Abstract: Objective Human papillomavirus (HPV) infects millions of men and women annually and is a substantial contributing factor in many cancers including oral, penile, anal, and cervical. Vaccination can reduce risk but adherence nationwide and, particularly in highly religious states, is suboptimal. Religious principles of abstinence before marriage and total fidelity following marriage may create a belief of protection through adherence to religious guidelines. However, while one partner may remain monogamous, one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 31 publications
3
24
1
Order By: Relevance
“…Several studies have found that parents who had discussed sexual health with their sons were more likely to vaccinate [ 35 , 36 ]. On the other hand, many parents were afraid that the HPV vaccine would promote promiscuity [ 37 ], and fathers especially were more likely to link risk to female promiscuity [ 38 ]. Furthermore, parents believed that vaccination was not needed since the child was too young and was not sexually active [ 21 , 37 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that parents who had discussed sexual health with their sons were more likely to vaccinate [ 35 , 36 ]. On the other hand, many parents were afraid that the HPV vaccine would promote promiscuity [ 37 ], and fathers especially were more likely to link risk to female promiscuity [ 38 ]. Furthermore, parents believed that vaccination was not needed since the child was too young and was not sexually active [ 21 , 37 , 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, many parents were afraid that the HPV vaccine would promote promiscuity [ 37 ], and fathers especially were more likely to link risk to female promiscuity [ 38 ]. Furthermore, parents believed that vaccination was not needed since the child was too young and was not sexually active [ 21 , 37 , 39 , 40 ]. However, it should be noted that parents tend to overestimate the age of sexual debut for their adolescent children [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other sociodemographic and ideological predictors of Americans’ attitudes toward vaccines overlap in ways specific to black and Hispanic Americans (e.g., misinformation about vaccines, lack of trust in medical authorities), they often come from different tributaries. For example, Americans who are more religious by various indicators are more likely to delay vaccination (Callaghan et al 2019; Rosen et al 2017), possibly because of a lack of trust in experts (Streefland et al 1999), a lack of knowledge about various vaccines (Birmingham et al 2019), or concerns about moral issues related to whether the vaccine requires cell lines derived from an aborted fetus (Pelčić et al 2016; Wombwell et al 2015) or that vaccination would indirectly promote premarital sex as in the HPV vaccine (Shelton et al 2013). Similarly, Americans who are more politically conservative, either by ideology or by party affiliation, tend to hold greater skepticism toward vaccines and to be more likely to delay update (Callaghan et al 2019; McCoy 2020), also because of lower levels of trust in government and experts (Baumgaertner, Carlisle, and Justwan 2018; Kahan et al 2010; Mesch and Schwirian 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Strong beliefs in sexual abstinence also play a role in HPV vaccination decisions. Survey studies have shown an inverse correlation between level of religious commitment and HPV vaccination coverage [ 22 , 23 ]. Furthermore, mediation analyses evaluating the relationship between religious beliefs, sexual activity and HPV vaccination among young adult women showed that sexual activity fully mediated the association between religious beliefs and HPV vaccination status [ 23 ].…”
Section: Discussionmentioning
confidence: 99%